2015
DOI: 10.1097/igc.0000000000000379
|View full text |Cite
|
Sign up to set email alerts
|

Fimbrial Cells Exposure to Catalytic Iron Mimics Carcinogenic Changes

Abstract: Our model aimed at studying the main nongenetic risk factor for ovarian cancer, providing an alternative interpretation for the role of menstruation in increasing risk of this pathology. This in vitro model mimics several features of the precursor lesions and opens new scenarios for further investigations regarding the correlation between damages produced by repeated retrograde menstruation carcinogenic stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…The cells cultured in chamber slides were fixed using an iced fixative solution (3.7 % formaldehyde, 3 % sucrose in PBS 1X) for 20 min at RT, permeabilized with ice 0.5 % Triton X-100 in PBS 1X in ice at 4 °C for 20 min, incubated with 3 % hydrogen peroxide in PBS 1X for 8 min and then maintained in a blocking solution (PBS 1X with 3 % albumin from bovine serum-BSA, Sigma, Milan, Italy) for 1 h in at RT, as previously described [ 36 ]. After this time the slides were incubated overnight at 4 °C in a humidified chamber with specific primary antibody VDR receptor (1:50).…”
Section: Methodsmentioning
confidence: 99%
“…The cells cultured in chamber slides were fixed using an iced fixative solution (3.7 % formaldehyde, 3 % sucrose in PBS 1X) for 20 min at RT, permeabilized with ice 0.5 % Triton X-100 in PBS 1X in ice at 4 °C for 20 min, incubated with 3 % hydrogen peroxide in PBS 1X for 8 min and then maintained in a blocking solution (PBS 1X with 3 % albumin from bovine serum-BSA, Sigma, Milan, Italy) for 1 h in at RT, as previously described [ 36 ]. After this time the slides were incubated overnight at 4 °C in a humidified chamber with specific primary antibody VDR receptor (1:50).…”
Section: Methodsmentioning
confidence: 99%
“…Iron deposits have also been identified in the fallopian tube (Seidman, 2013). Fimbrial secretory epithelial cells treated with increasing doses of iron elicited increased cellular proliferation along with changes in p53, MAPK, AKT, and c-Myc proteins, as well as increased ROS species (0.05–100mM) (Lattuada et al, 2015). Furthermore, vitamin D3 could oppose the oxidative stress-induced events mediated by iron in these fimbrial cells (Uberti et al, 2016).…”
Section: Initiation Of Ovarian Cancer By Persistent Oxidative Strementioning
confidence: 99%
“…It has recently been demonstrated that Fe 3+ , derived from menstrual reflux, recently defined as “incessant menstruation” [ 25 ], is able to induce an increase in fimbrial cell viability and proliferative capacity and to activate principal oncogenes (p53, pan-Ras, Ki67 and c-Myc). So, it has been confirmed that Fe 3+ is capable to induce carcinogenic changes and represents the main non-genetic risk factor for ovarian cancer [ 26 ]. For this reason, Fe 3+ can be considered a putative candidate as a transforming agent from normal human fimbrial cells into cancer cells maintaining physiological conditions of the menstrual cycle through oxidative stress and consequent oncogenes activations.…”
Section: Introductionmentioning
confidence: 99%
“…This research was planned to study the role of VitD to prevent oxidative injury induced by Fe 3+ exposition in primary fimbrial cells culture, because recent studies have hypothesized that fimbrial fallopian tubes are the site where most serous ovarian cancers develop [ 27 , 28 ], and the cells are subjected, to a constant carcinogenic stimulus represented by Fe 3+ [ 26 ], especially in presence of low levels of serum VitD.…”
Section: Introductionmentioning
confidence: 99%